The selective preparation and Suzuki coupling reactivity of cyclic 1,3-dione derived mono- and ditriflates - Willis, M; Claverie, C (2001)
The combination of triflic anhydride and 2,6-di-tert-butyl-4-methylpyridine was found to be a selective reagent system for the conversion of cyclic 1,3-diones to the corresponding monotriflate derivatives. The use of N-(5-chloro-2-pyridyl)triflimide together with KHMDS was selective for the preparation of the corresponding ditriflates. The Suzuki coupling reactivity of both the mono- and ditriflates was also explored. © 2001 Elsevier Science Ltd.